A Proposal Of Muda Indicator Agent To Estimate Lean Manufacturing Verification - Mohamad, Effendi; Ito, Teruaki; Yuniawan, Dani; Ibrahim, Mohamad Amran; Saptari, Adi; Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Shibghatullah, Abdul Samad; Md Ali, Mohd Amran (Penerbit UTeM, 2014)
-